Effects of an integrated health education and elastic band resistance training program on physical function and muscle strength in community‐dwelling elderly women: Healthy Aging and Happy Aging II study. Issue 5 (3rd May 2016) - Oh, Seung‐Lyul; Kim, Hee‐jae; Woo, Shinae; Cho, Be‐Long; Song, Misoon; Park, Yeon‐Hwan; Lim, Jae‐Young; Song, Wook
Abstract : Aim: In the present study, we determined the effect of an integrated health education and elastic band resistance training program on body composition, physical function, muscle strength and quality in community‐dwelling elderly women. Methods: We recruited participants with eligibility inclusion criteria, and randomly assigned them to either the control group ( n  = 19) or the intervention group ( n  = 19). The integrated intervention program comprised of health education and individual counseling, and elastic band training for 18 weeks (8 weeks of supervised training and 10 weeks of self‐directed training). We assessed body composition, muscle strength and quality, and physical function at pre‐, after 8 weeks (mid‐) and 18 weeks (post‐training). Results: After the intervention, there were no significant changes in skeletal muscle index, fat free mass, total lean mass and total fat mass for both the control group and intervention group. However, the interaction effect was significantly different in SPPB score ( P  < 0.05), isokinetic strength (60 deg/s, P  < 0.001; 120 deg/s; P  < 0.05) and muscle quality ( P  < 0.05) after 18 weeks of intervention relative to the baseline of the control and intervention groups. The supervised elastic band training of 8 weeks did not improve short physical performance battery score and isokinetic strength, whereas there was a significant increase of those outcomes (10.6% improvement, 9.8~23.5% improvement) after 10 weeks of following self‐directed exercise compared with the baseline. Conclusions: These results show the effectiveness of following self‐directed resistance training with health education after supervised training cessation in improvement of short physical performance battery and leg muscle strength. This intervention program might be an effective method to promote muscle strength and quality, and to prevent frailty in elderly women.Geriatr Gerontol Int 2017; 17: 825‐833 .